A new amplification strategy for a quartz crystal microbalance miRNA sensor based on selective interactions between a metal–organic framework and miRNA. (16th January 2020) - Ma, Ding; Zheng, Sheng-Run; Fan, Jun; Cai, Song-Liang; Dai, Zong; Zou, Xiao-Yong; Teng, Shao-Hua; Zhang, Wei-Guang
Abstract : UiO-66 is used as an effective amplifier in a QCM miRNA sensor to detect Let-7a. Abstract : A new strategy of using a MOF as an effective amplifier in a QCM miRNA sensor was presented based on the selective interaction between a MOF (UiO-66) with different zeta potentials and different miRNAs. The signal can be significantly enhanced, which leads to significantly improved performance in miRNA detection.